2008
DOI: 10.1051/0004-6361:20079001
|View full text |Cite
|
Sign up to set email alerts
|

Indications for 3 Mpc-scale large-scale structure associated with an X-ray luminous cluster of galaxies at z = 0.95

Abstract: Context. X-ray luminous clusters of galaxies at z ∼ 1 are emerging as major cosmological probes and are fundamental tools to study the cosmic large-scale structure and environmental effects of galaxy evolution at large look-back times. Aims. We present details of the newly-discovered galaxy cluster XMMU J0104.4-0630 at z = 0.947 and a probable associated system in the LSS environment. Methods. The clusters were found in a systematic study for high-redshift systems using deep archival XMM-Newton data for the se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…The differences in galaxy properties found by ourselves between the high density region, the low density region, and the field are consistent with the density relations found at z ∼ 1 by Smith et al (2005) and Postman et al (2005), at z = 1.24 by Demarco et al (2007), and at z = 1.5 by Fassbender et al (2008): red early-types dominate the cluster core, while blue late-types are found in the outskirts of the cluster.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The differences in galaxy properties found by ourselves between the high density region, the low density region, and the field are consistent with the density relations found at z ∼ 1 by Smith et al (2005) and Postman et al (2005), at z = 1.24 by Demarco et al (2007), and at z = 1.5 by Fassbender et al (2008): red early-types dominate the cluster core, while blue late-types are found in the outskirts of the cluster.…”
Section: Discussionsupporting
confidence: 91%
“…Early observations of cluster galaxies out to z = 0.5 by, for example, Butcher & Oemler (1978, 1984 showed little evidence of evolution in the colours of the red cluster population, but detected an increase in the fraction of blue galaxies, which appeared to avoid the cluster centre. Although this Butcher-Oemler effect has been disputed, the general conclusion still stands (e.g., Ellingson et al 2001;Tanaka et al 2005;Andreon et al 2006;Tran et al 2007;Fassbender et al 2008). Balogh et al (2007) find that, for a given stellar mass and redshift, fewer galaxies in groups show strong [O ii] emission than in field galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…On the X-ray side, new identifications of X-ray luminous clusters are currently largely driven by XMM-Newton serendipitous surveys (e.g. Mullis et al 2005;Stanford et al 2006;Fassbender et al 2008;Santos et al 2009;Schwope et al 2010) and smaller dedicated surveys of a A&A 527, A78 (2011) few square degrees (e.g. Andreon et al 2005;Bremer et al 2006;Pierre et al 2006;Finoguenov et al 2007Finoguenov et al , 2010Tanaka et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The XDCP has been very successful, so far providing 18 clusters at z > 0.8 and 10 clusters with z > 1 including five redshift confirmations from other projects (for selected results see e.g. Fassbender et al 2008;Santos et al 2009;Rosati et al 2009). …”
Section: Introductionmentioning
confidence: 90%
“…To obtain a well-defined sample of clusters at high redshift, z > 0.8, we started the XDCP (XMM-Newton Distant Cluster Project, Böhringer et al 2005;Fassbender et al 2008;Mullis et al 2005) based on archival XMM-Newton X-ray data. The XDCP has been very successful, so far providing 18 clusters at z > 0.8 and 10 clusters with z > 1 including five redshift confirmations from other projects (for selected results see e.g.…”
Section: Introductionmentioning
confidence: 99%